2019
DOI: 10.1371/journal.pone.0225067
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of parity on lung function data (LFD) of healthy females aged 40 years and more issued from an upper middle income country (Algeria): A comparative study

Abstract: BackgroundStudies evaluating the impacts of parity on LFD of healthy females presented controversial conclusions.AimTo compare the LFD of healthy females broken down according to their parities.MethodsA medical questionnaire was administered and anthropometric data were determined. Two groups [G1 (n = 34): ≤ 6; G2 (n = 32): > 6] and three classes [C1 (n = 15): 1–4; C2 (n = 28): 5–8; C3 (n = 23): 9–14] of parities were identified. LFD (plethysmography, specific airway resistance (sRaw)] were determined. Student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Due to these underlying sex differences, it is plausible that the effects of disease on PFTPs will also differ. These differences may also be related to other internal or external factors as previously documented in the published literature [2][3][4][5][6][7][8][9][10][26][27][28][29]. However, it was beyond the scope of this current study to explore other potential factors contributing to sex differences in PFTPs in our study patients.…”
Section: Discussionmentioning
confidence: 80%
“…Due to these underlying sex differences, it is plausible that the effects of disease on PFTPs will also differ. These differences may also be related to other internal or external factors as previously documented in the published literature [2][3][4][5][6][7][8][9][10][26][27][28][29]. However, it was beyond the scope of this current study to explore other potential factors contributing to sex differences in PFTPs in our study patients.…”
Section: Discussionmentioning
confidence: 80%
“…This point was clearly foreseen by the GLI Task Force noting that the derived GLI-2021 norms may not be appropriate for individuals of ‘non-European’ ancestry [ 7 ]. The second explanation is related to the effects of parity on SLVs [ 4 , 14 ]. A previous Algerian study [ 14 ] reported that compared to females with a parity ≤ 6, those with a parity > 6 had higher FRC and RV.…”
Section: Discussionmentioning
confidence: 99%
“…The second part [ 12 ] aimed at testing the validity of the Eastern Algeria plethysmographic norms [ 11 ]. The third part [ 14 ] aimed at evaluating the impact of parity on females’ plethysmographic data. The fourth part constitutes the topic of this study.…”
Section: Population and Methodsmentioning
confidence: 99%
See 2 more Smart Citations